A THIRD REVOLUTION IN FAMILY DISPUTE RESOLUTION: ACCESSIBLE LEGAL PROFESSIONALISM - Semple, Noel (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2017)
Innovation in family law firms can tangibly improve access to justice in Canada. This article develops that claim by drawing on empirical data and scholarship about Canadian family law. Part 1 explains how and why legal needs arising from the dissolution of intimate relationships are so difficult for the parties to meet.  This Part draws on civil legal needs surveys, surveys with lawyers, and data from interviews with litigants. The focus shifts to family law firms (including sole practitioners) in Part 2, using new empirical data about the Canadian lawyers who do this work. Three promising opportunities to innovate for accessibility in family law practice are identified: (i) innovative fee structure; (ii) innovative service variety; and (iii) innovative division of labour. A "third revolution" in Canadian family law is proposed in Part 3.  Our family law doctrine was revolutionized beginning in the 1960s, and family law alternative dispute resolution was similarly transfigured beginning in the 1980s. It is now time to foment a third revolution, in family law practice accessibility, to bring the benefits of family justice to all Canadians who need them.